2014
DOI: 10.2514/1.b35195
|View full text |Cite
|
Sign up to set email alerts
|

Velocimetry Measurements of a Scramjet Cavity Flameholder with Inlet Distortion

Abstract: Particle image velocimetry measurements were made along the center plane of a scramjet cavity flameholder to analyze simulated inlet flow distortion in the direct-connect test environment. Mach 3 nonreacting tests examined an oblique shock impinging upon locations in-and upstream of the cavity, including cases with wall-normal air injection upstream of the cavity to simulate fuel injection. Addition of flow distortion altered the size and shape of the primary recirculation region within the cavity by deflectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…It is reported that a low-speed recirculation region can be created in a cavity in supersonic combustion, and partial subsonic combustion within the recirculation flow acts as a continuous ignition source for the whole flow, thus eventually achieving flameholding in supersonic incoming flows [23][24][25]. Because of pressure oscillations resulting from the subsonic combustion, as shown in Fig.…”
Section: B Detonation Sustainment and Forward Propagationmentioning
confidence: 99%
“…It is reported that a low-speed recirculation region can be created in a cavity in supersonic combustion, and partial subsonic combustion within the recirculation flow acts as a continuous ignition source for the whole flow, thus eventually achieving flameholding in supersonic incoming flows [23][24][25]. Because of pressure oscillations resulting from the subsonic combustion, as shown in Fig.…”
Section: B Detonation Sustainment and Forward Propagationmentioning
confidence: 99%
“…Most recently, an advantage of the scheme based on an impinging shock wave (SW) for flow control and promotion of fuel ignition in the cavity of a supersonic combustor has been demonstrated experimentally [6,7,8,9,10]. Typically the shock wave was initiated by a mechanical obstacle (short wedge) installed on the wall opposite the cavity which modified the flowfield inside of it.…”
Section: Introductionmentioning
confidence: 99%
“…5 Optical diagnostics applied to scramjet flows have included planar laser-induced fluorescence (PLIF), 6 coherent antiStokes Raman spectroscopy (CARS), 7 tunable diode laser absorption spectroscopy (TDLAS), 8 tunable diode laser absorption tomography (TDLAT), 9 laser Doppler velocimetry (LDV), 10 hydroxyl-tagging velocimetry (HTV), 11 and particle image velocimetry (PIV). 1,[12][13][14][15][16] Of the velocimetry techniques, both PIV and LDV are dependent on proper seeding of the flowfield with tracer particles. 17 These particles must be sufficiently large to scatter enough light to enable photographic detection, yet small enough to faithfully track the flow.…”
Section: Introductionmentioning
confidence: 99%